2002
DOI: 10.1088/0953-4075/35/11/314
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact ionization studies for SF5CF3

Abstract: Electron impact ionization cross sections measured close to threshold are reported for the newly discovered greenhouse gas SF5CF3. No stable parent ion is detected but several cations are detected and their appearance energies (AE) have been measured. The AE (CF3+/SF5CF3) = 12.87±0.10 eV is in excellent agreement with a recently reported value derived from a photoelectron-photoion coincidence experiment. Other ion thresholds are: AE (CF+/SF5CF3) = 24.44±0.10 eV, AE (CF2+/SF5CF3) = 17.80±0.50 eV; AE (SF+/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…The electron energy loss spectrum (EELS) of SF 5 CF 3 has recently been measured and revealed that the threshold for the lowest-lying excited electronic state lies B8 eV above the ground state Mason, 2001, 2003, respectively), confirming the prediction of a high dissociation energy for the SF 5 -CF 3 bond (Gstir et al, 2002) of about 4 eV.…”
mentioning
confidence: 64%
“…The electron energy loss spectrum (EELS) of SF 5 CF 3 has recently been measured and revealed that the threshold for the lowest-lying excited electronic state lies B8 eV above the ground state Mason, 2001, 2003, respectively), confirming the prediction of a high dissociation energy for the SF 5 -CF 3 bond (Gstir et al, 2002) of about 4 eV.…”
mentioning
confidence: 64%
“…The ionization energy is 11.8 eV. It was determined by fitting the measured data by a Wannier-like threshold law [23,24]. …”
Section: Methodsmentioning
confidence: 99%
“…Since 2000, there have been a large number of new studies, some of direct importance to the atmospheric properties of SF 5 CF 3 , some of more general and pure scientific interest. They include VUV and XUV absorption [4,[15][16][17][18][19], valence photoelectron [4,15,[20][21][22], electron energy loss spectroscopy [4,23], electron scattering [24][25][26], protonation [27] and photofragmentation studies [20][21][22]28].…”
Section: Structure Spectroscopy and Thermochemistry Of Sf 5 Cfmentioning
confidence: 99%
“…The electron energy loss spectrum [23] [20,22], driven by the large and negative enthalpy of formation of CF 4 , but the significant re-arrangement of chemical bonds needed in the transition state makes this reaction kinetically unfavourable.) Taking SF 5 CF 3 as an example, we can define the first dissociative ionisation energy (DIE)…”
Section: 1mentioning
confidence: 99%